Antagonic activities of Trypanosoma cruzi metacaspases affect the balance between cell proliferation, death and differentiation - Laverriere, Marc (2012)
Metacaspases are distant relatives of animal caspases present in plants, fungi and protozoa. At variance with caspases, metacaspases exhibit stringent specificity for basic amino-acid residues and are absolutely dependent on millimolar concentrations of calcium. In the protozoan parasite Trypanosoma cruzi, metacaspases have been suggested to be involved in an apoptosis-like phenomenon upon exposure of the parasite to fresh human serum (FHS). Nuclear relocalization of metacaspases was observed after FHS treatment and overexpression of metacaspase-5 led to enhanced sensitivity to this stimulus. Here we report some biochemical properties of T. cruzi metacaspases. Performing fluorescent-activated cell sorting (FACS) analysis of epimastigotes inducibly overexpressing metacaspase-3, we demonstrate a role for this metacaspase in cell cycle progression, protection of epimastigotes from naturally occurring cell death and differentiation to infective metacyclic trypomastigotes. We also show that regulation of metacaspase-3 activity is important for cell cycle completion inside the mammalian host. On the other hand, inducible overexpression of metacaspase-5 lacking its C-terminal domain caused an apoptotic-like response. These results suggest that the two T. cruzi metacaspases could play an important role in the life cycle and bring to light the close relationship between cell division, death and differentiation in this ancient unicellular eukaryote. © 2012 Macmillan Publishers Limited All rights reserved.